Causes of Ecological Crisis and the Necessity of Ecological Education in the Encyclical Laudato Si’ - Ante Bekavac (Nova Prisutnost, 2023)
The modern ecological crisis that today radically affects people and the nature reveals the deeper causes that lie within people themselves. First of all, people no longer understand themselves in the key of creation, they no longer understand themselves and the created world as gifts from the Creator, but are intoxicated with power combined with technology and science in the instrumental-rational key and understand themselves as the sole creators of their own fates. Relying on the hermeneutic key to understanding creation, Pope Francis starts from the Creator and exposes this crucial anthropological fallacy, the price of which has unforeseeable effects on the created reality. The paper points out the fundamental problems and difficulties of the modern ecological crisis, seeking to show that it is actually hidden in the crisis of the humanity. Following the contemplations and ideas that Pope Francis presented in the encyclical Laudato Si’, the paper seeks to highlight the neuralgic points of the contemporary ecological crisis by showing ways out of the labyrinth of anthropological self-sufficiency. The need for and importance of education for environmental awareness, i.e., a responsible, mature and moral approach to created reality, are emphasized. In the final part of the paper, the rapprochement to freedom is highlighted, in line with the human dignity that has its source in God the Creator. Answering the question of why ecological education is important and crucial, the conclusion shows that it is the only right path of authentic humanity that bears the mark of creation in God’s image, and that people are called to act responsibly towards the created reality.